Monday

March 30, 2015

March 30, 2015

Posted by **jessica** on Tuesday, July 26, 2011 at 5:17pm.

- Math -
**Reiny**, Tuesday, July 26, 2011 at 7:57pmhave you learned the sum and product property of quadratics? If so , this is easy

sum = 3+√3 + 3-√3 = 6

product = (3+√3)(3-√3) = 9 - 3 = 6

equation: x^2 - 6x + 6 = 0

if not ...

expand

(x - (3+√3))(x - (3-√3))= 0

you will get the same answer as above

**Answer this Question**

**Related Questions**

algebra - (1) if root x-a/x-b + a/b = root x-b/x-a + b/a, b not equal to a, then...

physics - two forces F1 and F2 acting at a point have a resultant F. If F2 is ...

Math - Can someone please check my answers! 2. Find value of cos(255degrees)cos(...

Pre-Calculus(Trigonometry) - An 8-m boom is used to move a bundle of piping from...

maths - find the equation of a straight line on which the perpendicular from the...

Calculus - Find the indicated limit. lim_(x->-63.5)(root3(2x + 2))

Algebra - Given that f(x) = x^2-3 and g(x) = 2x+1, find each of the following, ...

Algebra - Given that f(x) = x^2-3 and g(x) = 2x+1, find each of the following, ...

Math - (root2 + root3)^2 simplify

Pre-Calc - How would you go about finding all the solutions of the equation. I ...